Understanding the discrete element method : simulation of non-spherical particles for granular and multi-body systems - Matuttis, Hans-Georg; Chen, J. F. (Jian-Fei), 1963- (Singapore : Wiley, 2014)
Gives readers a more thorough understanding of DEM and equips researchers for independent work and an ability to judge methods related to simulation of polygonal particles Introduces DEM from the fundamental concepts (theoretical mechanics and solidstate physics), with 2D and 3D simulation methods for polygonal particlesProvides the fundamentals of coding discrete element method (DEM) requiring little advance knowledge of granular matter or numerical simulationHighlights the numerical tricks and pitfalls that are usually only realized after years o.
2.2.6 Implicit Euler method2.3 Runge-Kutta methods; 2.3.1 Adaptive step-size control; 2.3.2 Dense output and event location; 2.3.3 Partitioned Runge-Kutta methods; 2.4 Symplectic methods; 2.4.1 The classical Verlet method; 2.4.2 Velocity-Verlet methods; 2.4.3 Higher-order velocity-Verlet methods; 2.4.4 Pseudo-symplectic methods; 2.4.5 Order, accuracy and energy conservation; 2.4.6 Backward error analysis; 2.4.7 Case study: the harmonic oscillator with andwithout viscous damping; 2.5 Stiff problems; 2.5.1 Evaluating computational costs; 2.5.2 Stiff solutions and error as noise.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Granular flow; Discrete element method; Multibody systems; Mechanics, Applied -- Computer simulation; Discrete element method; Granular flow; Mechanics, Applied -- Computer simulation; Multibody systems; SCIENCE -- Mechanics -- General; SCIENCE -- Mechanics -- Solids; Electronic books